Indian capital control liberalization: Evidence from NDF markets - Michael Hutchison; Jake Kendall; Gurnain Pasricha; Nirvikar Singh (University of California, Santa Cruz Institute for International Economics (SCIIE), 2008)
This paper analyzes the extent to which the effectiveness of capital controls in India have changed over time. We begin by calculating deviations from covered interest parity utilizing data from the 3-month offshore non-deliverable rupiah forward (NDF) market. Then, using the self-exciting threshold autoregression methodology, we estimate a no-arbitrage band whose boundaries are determined by transactions costs and by the effectiveness of capital controls. Inside the bands, small deviations from CIP follow a random walk process. Outside the bands, profitable arbitrage opportunities exist and we estimate an adjustment process back towards the boundaries. We identify three distinct periods, and estimate the model over each sub-sample in order to capture the de facto effect of changes in capital controls over time. We find that de facto capital control barriers: (1) are asymmetric over inflows and outflows, (2) have changed over time from primarily restricting outflows to effectively restricting inflows; (3) arbitrage activity closes deviations from CIP when the threshold boundaries are exceeded in all sub-samples. In recent years, capital controls have been more symmetric over capital inflows and outflows and the deviations from CIP outside the boundaries are closed more quickly.
Keywords: 330; Kapitalmarktregulierung; Kapitalmobilität; Transaktionskosten; Kapitalertrag; Marktsegmentierung; Schätzung; Indien